2020
DOI: 10.21203/rs.3.rs-116225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of non-daily and daily cannabis use among persons 15 years and older in South Africa: Results of a national survey in 2017

Abstract: BackgroundThe study aimed to assess the prevalence and correlates of non-daily and daily cannabis use among persons 15 years and older in South Africa.MethodIn a national cross-sectional 2017 survey, 39,207 persons 15 years and older (Median = 34 years) responded to a questionnaire on substance use and health variables. Multinominal logistic regression was used to assess the determinants of nondaily and daily cannabis use and logistic regression for the determinants of daily cannabis use among active cannabis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Reasons for the overall slight increase of HHDA and increase in any drug use in South Africa from 2008 or 2012 to 2017 need further research. 25 In agreement with previous studies, 6,7,8,14,26,27 this study found that male sex increased the odds and older age decreased the odds of HHDA and drug use. Sex-specific role expectations and norms, such as associating drinking alcohol and drug use with masculinity, may be related to the male preponderance of HHDA and drug use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Reasons for the overall slight increase of HHDA and increase in any drug use in South Africa from 2008 or 2012 to 2017 need further research. 25 In agreement with previous studies, 6,7,8,14,26,27 this study found that male sex increased the odds and older age decreased the odds of HHDA and drug use. Sex-specific role expectations and norms, such as associating drinking alcohol and drug use with masculinity, may be related to the male preponderance of HHDA and drug use.…”
Section: Discussionsupporting
confidence: 92%
“…Reasons for the overall slight increase of HHDA and increase in any drug use in South Africa from 2008 or 2012 to 2017 need further research. 25 …”
Section: Discussionmentioning
confidence: 99%